ANALISIS PERILAKU AMAN PADA PEKERJA KONSTRUKSI DENGAN PENDEKATAN BEHAVIOR-BASED SAFETY (STUDI DI WORKSHOP PT. X JAWA BARAT) - Fransisca Anggiyostiana Sirait; Indriati Paskarini (Universitas Airlangga, 2016)
PT. X is a company in steel structure construction and fabricator pole field. In the company’s Workshop, there are bending, shearing, and cutting processes. The basic causation of work accident are unsafe behavior and unsafe condition. This research aims to analyze the safe behavior of construction workers with Behavior-Based Safety approach in the stage of define and observe of The DO IT Process, with the ABC (Activator, Behavior, and Consequence) model. This is an observational descriptive research with the cross-sectional design. The respondents of this research are 30 construction workers in Workshop of PT. X. The results of this research showed that all workers have good awareness; 93,3% of construction workers have good knowledge; 93,1% have good perception; 92,7% have good motivation; 93,3% stated that the safety needs had been fulfilled; 93,3% of construction workers stated that the existing safety rules of the company had been implemented; 90% of construction workers ever got positive reinforcement; 85,7% of construction workers ever got punishment; the construction workers stated that safety training and management role of the company had been implemented. The result also showed the construction workers largely did safety behavior at work. In order to improve safe behavior, the company needs to give training to all construction workers, implement SOP consistently, evaluate and monitor the worker’s behavior, and implement the Behavior-Based Safety program (The DO IT Process).Keywords: safe behavior, behavior-based safety, construction company